Is robotic da Vinci Xi (R) superior to the da Vinci Si (R) for sphincter-preserving total mesorectal excision? Outcomes in 150 mid-low rectal cancer patients - Aliyev, Vusal; Arslan, Naciye Çiğdem; Göksoy, Beslen; Güven, Koray; Göksel, Süha; Asoğlu, Oktar (Springer Nature, 2022)
The aim of this study was to determine the superiority between the robotic da Vinci Si (R) (Si group) and da Vinci Xi (R) (Xi group) generation in patients with mid-low rectal cancer. Between December 2011 and December 2017, 88 patients with mid-low rectal cancer were operated on using the Si robotic system, from January 2018 to May 2021, 62 more patients with mid-low rectal cancer were operated on using the Xi robotic system. Perioperative and postoperative short-term outcomes were compared between the two groups. Univariate and multivariate Cox-regression analysis were performed to determine factors affecting operating time. A cumulative sum (CUSUM) analysis was also performed to determine the learning curve of the primary surgeon. All patients underwent sphincter saving total mesorectal excision (TME). The overall operating time was significantly shorter in the Xi group (181.3 +/- 31.8 min in Si group vs 123.6 +/- 25.7 min in the Xi group, p < 0.001). There were no significant differences in terms of conversion rates, mean hospital stays, complications and histopathologic data. CUSUM analysis show completion of learning curve in 44th case of Si group. Univariate and multivariate analysis demonstrated that the learning curve of the primary surgeon (p < 0.001) and the type of robotic system (Xi) are only two factors associated with operating time (OR, 95% CI p; 3.656, 0.665-9.339, p < 0.001). Our study found that the robotic da Vinci Xi systems provide significantly shorter operating time comparing with Si systems, when performing sphincter-preserving TME in mid-low rectal cancer patients. Surgical system (da Vinci Xi) and primary surgeon learning curve are two independent risk factors which associated shortened operating time. Postoperative complication rates and histopathologic outcomes are similar in both groups.
Keywords: Rectal Cancer; Robotic Surgery; Total Mesorectal Excision; Operating Time; Learning Curve